Perilaku Online Beresiko Remaja Hubungannya dengan Kualitas Hidup dan Mediasi Orang Tua - Zulfa Febriani; Octaviani Indrasari Ranakusuma (Lembaga Penelitian Universitas YARSI, 2020)
Adolescents in urban area of Indonesia have become the highest internet users. Most of them were social media consumers. The high usage could make them involve in risky online behavior, which included giving personal information and accessing sexual content. The activities could affect to adolescents’ permissiveness about sexuality and interfere with their psychological development. Among the factors associated to risky behavior were parental monitoring and adolescent psychososial condition, but there was not many study in Indonesia that directly see the role of the factors in adolescents’ risky sexual online behavior. Therefore, the study aimed to know wheater adolescents’ quality of life and parental mediation contributed to their risky sexual online behavior. This associative research had included 148 adolescents in Jakarta by accidental sampling technique. We used EU KIDS ONLINE sub parental mediation, online risky activity, risky sexual activity and KIDSCREEN-27 as instrument. The study indicated that parental technical mediation and physical activity and health associated to risky sexual activity as the perpetator. The result should be generalized with caution to adolesecence population in Jakarta as the sample and data were not normally distributed. Any research of the same topic should consider the sample representativeness and social desireability of the risky sexual online behavior scale. Literacy about the safety of technical internet use and interaction needs to be increased.